The role of the Sabhara Patrol Unit (Hunter Team) in order to prevent cases of theft of motorized vehicles in the legal area of the Palembang Police - Dendi Eriyan (Advances in Police Science Research Journal, 2022)
The crime of theft often occurs in the city of Palembang. It was recorded that in the last 3 years the ranking of motor vehicle theft cases was ranked the 2nd most in criminal cases. This raises anxieties for the people of Palembang city who are victims and feel very disadvantaged by the event. The theories and concepts that the author uses in this study are based on management theory by George R. Terry, role theory by Paul B. Horton, routine activity theory. by Marcus Felson and Robert K. Cohen, the concept of theft, the concept of crime prevention, the concept of patrol and Perkabaharkam No. 1 of 2017 concerning patrols. This study uses a qualitative approach and field study methods. The sources used are primary and secondary sources. Data collection techniques used are interviews, observation, and document research. The results obtained by the author during the study are that all actions of members of the Palembang Polrestabes Sabhara unit have prioritized preventive measures, namely carrying out routine patrols using KRYD (improved routine activities), namely the Hunter Team. However, there are still many obstacles due to the lack of personnel, quality of human resources, inadequate infrastructure, and lack of public awareness to protect personal property. The suggestions submitted by the author are to give strict sanctions, add personnel, improve infrastructure and improve their abilities by following the Dikjur.